Desarrollo de un aplicativo web para la gestión de productos e historial clínico de pacientes aplicando analítica de datos en la Óptica "San José", ubicada en el cantón La Maná, provincia de Cotopaxi. - Pincay Llivigañay, Catalina Mishelle (2024)
The main objective of this project is to develop a web application for the "San José" Optician, in order to efficiently manage the products and patient history. This web application works as a tool dedicated directly to optical staff, facilitating product administration and patient management. In addition, the application shows graphs with data that directly support decision making. For its development, the MVC (Model-View-Controller) design pattern was used, along with PHP as a programming language, MySQL as a database and Power BI for data analysis. These modern technologies guarantee compatibility with multiple browsers, ensuring an intuitive and friendly user experience. The project will improve efficiency and precision in product management and patient care, providing a comprehensive tool that simplifies the daily tasks of optical staff. In addition, it focuses on the administrative field, which makes the optician more competitive by using data analytics to increase sales and attract new customers.